2013
DOI: 10.4103/2045-8932.109915
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus‐1 Transgene Expression Increases Pulmonary Vascular Resistance and Exacerbates Hypoxia‐Induced Pulmonary Hypertension Development

Abstract: Pulmonary arterial hypertension (PAH) is a progressive disease characterized by increased pulmonary arterial resistance and vessel remodeling. Patients living with human immunodeficiency virus-1 (HIV-1) have an increased susceptibility to develop severe pulmonary hypertension (PH) irrespective of their CD4+ lymphocyte counts. While the underlying cause of HIV-PAH remains unknown, the interaction of HIV-1 proteins with the vascular endothelium may play a critical role in HIV-PAH development. Hypoxia promotes PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 87 publications
2
24
1
Order By: Relevance
“…Increased survival of HIV-infected patients with the advent of antiretroviral therapy has resulted in an increase in the prevalence of noninfectious complications including pulmonary arterial hypertension (4244). Furthermore, illicit drug use has been identified as one of the most common risk factors in the individuals with HIV-associated PAH (9, 10, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Increased survival of HIV-infected patients with the advent of antiretroviral therapy has resulted in an increase in the prevalence of noninfectious complications including pulmonary arterial hypertension (4244). Furthermore, illicit drug use has been identified as one of the most common risk factors in the individuals with HIV-associated PAH (9, 10, 43).…”
Section: Discussionmentioning
confidence: 99%
“…However, neither MCAT nor SOD2 attenuated hypoxia-induced elevations in RVH. Numerous studies suggest that exposure to chronic hypoxia elevates RVSP which subsequently leads to elevated RVH [47, 48]. In contrast, we have previously observed that attenuation of hypoxia-induced RVSP reduces RVH [27] or has no effect on RVH [28].…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, Tat interacts with different types of receptors present on the surface of endothelial cells to induce VCAM-1 expression, p38 MAPK activation, nuclear factor-κB translocation, and increased expression of hypoxia-inducible factor-1α, which, collectively are involved in the pathogenesis of pulmonary vascular remodeling and dysfunction. 29 Tat may also bind VEGF and PDGF to increase local concentrations of these factors and this may explain the elevated levels of PDGF seen in lung biopsies of patients with HIV-associated PAH. 56 Similarly, elevated levels of PDGF have been found in patients with HIV infection and PAH, but not in HIV-infected individuals without PAH.…”
Section: Contemporary Hypothesesmentioning
confidence: 99%
“…Increased levels of the cytokine interleukin (IL)-2 and the HIV-1 coreceptor CCR5 are also attributed to Tat. Exposure of isolated endothelial cells in culture to viral proteins (mainly Tat and gp120) results in the accumulation of hypoxia-inducible factor-1α protein 29 that occurs concomitant with increases in platelet-derived growth factor-B (PDGF-B). In turn, both hypoxia-inducible factor-1α and PDGF-B initiate and sustain activation of metabolic and proliferation by guest on May 11, 2018 http://circ.ahajournals.org/ Downloaded from signaling pathways that are contribute to pulmonary vascular remodeling in HIV.…”
Section: Hiv Proteins and Hiv-related Factors That Mediate Pulmonary mentioning
confidence: 99%
See 1 more Smart Citation